A new species of the genus Floresorchestia (Crustacea, Amphipoda, Talitridae) from Chilika Lagoon, east coast of India - Bhoi, Gitanjali; Myers, Alan A.; Kumar, R. Kiran; Patro, Shesdev (Zootaxa, 2024)
Floresorchestiinae Myers & Lowry, 2020 is a recognizable group in the family Talitridae due to the distinctive presence of slits on their epimeral plates. A distinctive species of the genus Floresorchestia collected from Chilika Lagoon inhabiting the seaweed Gracilaria sp., Floresorchestia odishi sp. nov., can be distinguished from other species of the genus by the remarkably high number of slits on epimeron 2 (43–47) and epimeron 3 (21–24).